Peran Pancasila dalam Mendorong Keadilan Sosial bagi Karyawan di PT. Pharos Indonesia - Anggun Dinianti; Sahdan Mustari; Muhammad Syafri; Adi Hermawan; Irwan Irwan; Asran Asran (Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service program aims to improve the understanding and application of Pancasila values, especially the fifth principle, in promoting social justice for employees. Through a series of socialization and discussion activities, this program focuses on employee awareness of the importance of social justice in the work environment. The results of this activity show an increase in employee understanding of the application of Pancasila values ​​in work relationships, which is expected to create a fairer and more harmonious work atmosphere. This program emphasizes that the application of Pancasila values ​​in the world of work is a strategic step to realize social justice for all employees.